Injection of IK1 through dynamic clamp can make all the difference in patch-clamp studies on hiPSC-derived cardiomyocytes - Verkerk, Arie O.; Wilders, Ronald (Frontiers in Physiology, 2023)
Human-induced stem cell-derived cardiomyocytes (hiPSC-CMs) are a valuable tool for studying development, pharmacology, and (inherited) arrhythmias. Unfortunately, hiPSC-CMs are depolarized and spontaneously active, even the working cardiomyocyte subtypes such as atrial-and ventricularlike hiPSC-CMs, in contrast to the situation in the atria and ventricles of adult human hearts. Great efforts have been made, using many different strategies, to generate more mature, quiescent hiPSC-CMs with more close-to-physiological resting membrane potentials, but despite promising results, it is still difficult to obtain hiPSC-CMs with such properties. The dynamic clamp technique allows to inject a current with characteristics of the inward rectifier potassium current (IK1), computed in real time according to the actual membrane potential, into patch-clamped hiPSC-CMs during action potential measurements. This results in quiescent hiPSC-CMs with a close-to-physiological resting membrane potential. As a result, action potential measurements can be performed with normal ion channel availability, which is particularly important for the physiological functioning of the cardiac SCN5A-encoded fast sodium current (INa). We performed in vitro and in silico experiments to assess the beneficial effects of the dynamic clamp technique in dissecting the functional consequences of the SCN5A-1795insD +/− mutation. In two separate sets of patch-clamp experiments on control hiPSC-CMs and on hiPSC-CMs with mutations in ACADVL and GNB5, we assessed the value of dynamic clamp in detecting delayed afterdepolarizations and in investigating factors that modulate the resting membrane potential. We conclude that the dynamic clamp technique has highly beneficial effects in all of the aforementioned settings and should be widely used in patch-clamp studies on hiPSC-CMs while waiting for the ultimate fully mature hiPSC-CMs.